Philosophy of technology and nursing - Barnard, Alan (Nursing philosophy, 2002)
This paper outlines the background and significance of philosophy of technology as a focus of inquiry emerging within nursing scholarship and research. The thesis of the paper is that philosophy of technology and nursing is fundamental to discipline development and our role in enhancing health care. It is argued that we must further our responsibility and interest in critiquing current and future health care systems through philosophical inquiry into the experience, meaning and implications of technology. This paper locates nurses as important contributors to the use and integration of health care technology and identifies nursing as a discipline that can provide specific insights into the health experience(s) of individuals, cultures and societies. Nurses are encouraged to undertake further examination of epistemological, ontological and ethical challenges to arise from technology as a focus of philosophical inquiry. The advancement of philosophy of technology and nursing will make a profound contribution to inquiry into the experience of technology, the needs of humanity and the development of appropriate health care.